The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019 IEEE International Conference on Big Data (Big Data) 2019
DOI: 10.1109/bigdata47090.2019.9005967
|View full text |Cite
|
Sign up to set email alerts
|

Adaptively selecting occupations to detect skill shortages from online job ads

Abstract: Labour demand and skill shortages have historically been difficult to assess given the high costs of conducting representative surveys and the inherent delays of these indicators. This is particularly consequential for fast developing skills and occupations, such as those relating to Data Science and Analytics (DSA). This paper develops a data-driven solution to detecting skill shortages from online job advertisements (ads) data. We first propose a method to generate sets of highly similar skills based on a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Technologies of robots and artificial intelligence (AI) are expected to replace simple labor and make workplaces more skill-polarized [2,3]. Researchers tried to predict the future of the job market based on numerical data (e.g., labor employment [4] and statistics of graduates [5]) or textual data (e.g., job postings [6,7], job attributes [8], and Google trends [9]). However, these approaches were mainly focused on occupational data and limitedly considered changes in technology.…”
Section: A Job Forecastingmentioning
confidence: 99%
“…Technologies of robots and artificial intelligence (AI) are expected to replace simple labor and make workplaces more skill-polarized [2,3]. Researchers tried to predict the future of the job market based on numerical data (e.g., labor employment [4] and statistics of graduates [5]) or textual data (e.g., job postings [6,7], job attributes [8], and Google trends [9]). However, these approaches were mainly focused on occupational data and limitedly considered changes in technology.…”
Section: A Job Forecastingmentioning
confidence: 99%
“…A skill shortage tool was proposed in [122]; the tool detects skill shortages by correlating different features in the job ad such as its location, salary level and the job ad period being advertised. In [85], they developed a data-driven solution to detect skill shortages from online job ads data. To do so, they identified skills specific to data science and analysis, to capture the labor trends of such an occupation.…”
Section: ) Skill Mismatch and Alignmentmentioning
confidence: 99%
“…Therefore, workers to work on soft skills such as their learning ability, adaptability, communication skills, problem-solving and decision-making, teamwork, and creative capacity. Furthermore, 309,000 vacancies in 169 professions of various professional levels in the United Kingdom (UK) was analyzed [40]. The research indicated that employers found it difficult to recruit suitable workers in 106,000 of these positions.…”
Section: Research Backgroundmentioning
confidence: 99%